Winescape: Local Reinhabitation Narratives (The Case of Zielona Góra) - Mikołajczak, Małgorzata (Porównania, 2021)
Reinhabitation narratives are cultural-educational practices that involve restoring the “ecological imagination” of places through stories associated with them. The term proposed by Serenella Iovino in the field of bioregional studies, which refers to places disrupted and injured by exploitation, is applied to contemporary stories about Zielona Góra. The author shows how, in reference to the city’s German past, these stories reactivate its wine tradition and project the winescape as a taskscape (in Timothy Ingold’s sense). Under consideration are both the effects of the destruction of the pre-war heritage (in natural and social terms) and regeneration, which is accomplished through three strategies: appealing to the winescape as a space determined by the laws of nature (1), activating the bio-memory inscribed in the enographic biotopos (2), and reactivating the winescape through sensory experience (3). Responding to the contemporary crisis of ecological imagination, local reinhabitation narratives instantiate place and revive its cultural and ecological possibilities. They constitute an “anti-epic” that opens up the past and the future.